2001
DOI: 10.1002/etc.5620200422
|View full text |Cite
|
Sign up to set email alerts
|

Frequently co‐occurring pesticides and volatile organic compounds in public supply and monitoring wells, southern New Jersey, USA

Abstract: One or more pesticides were detected with one or more volatile organic compounds (VOCs) in more than 95% of samples collected from 30 public supply and 95 monitoring wells screened in the unconsolidated surficial aquifer system of southern New Jersey, USA. Overall, more than 140,000 and more than 3,000 unique combinations of pesticides with VOCs were detected in two or more samples from the supply and monitoring wells, respectively. More than 400 of these combinations were detected in 20% or more of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Moreover, drinking-water criteria currently are based on the toxicity of individual compounds and not combinations of compounds. The possibility that exposure to multiple organic compounds, even at low concentrations, may have a synergistic humanhealth consequence is an area of recent research (Birader and Rayburn, 1995;Marinovich et al, 1996), and the co-occurrence of organic compounds in drinking-water supplies has recently been documented (Stackelberg et al, 2001;Squillace et al, 2002). In this study, 11-17 different OWCs were detected in each of the four samples of finished water.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, drinking-water criteria currently are based on the toxicity of individual compounds and not combinations of compounds. The possibility that exposure to multiple organic compounds, even at low concentrations, may have a synergistic humanhealth consequence is an area of recent research (Birader and Rayburn, 1995;Marinovich et al, 1996), and the co-occurrence of organic compounds in drinking-water supplies has recently been documented (Stackelberg et al, 2001;Squillace et al, 2002). In this study, 11-17 different OWCs were detected in each of the four samples of finished water.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, the results of this study suggest that additional research on the toxicity of the target compounds should include not only the individual OWCs but also mixtures of these compounds. The prevalence of multiple compounds in water resources has been previously documented for other contaminants (52,53). In addition, research has shown that select chemical combinations can exhibit additive or synergistic toxic effects (54)(55)(56), with even compounds of different modes of action having interactive toxicological effects (57).…”
Section: Resultsmentioning
confidence: 99%
“…Shallower wells generally are considered more prone to anthropogenic contamination than deeper wells. Public supply wells can have high pumping rates and large capture zones, which can increase the number of potential contamination sources (8). Unconfined aquifers generally are considered more prone to contamination than confined aquifers.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, identification of common mixtures of contaminants in water can be viewed as a first step toward defining exposure. Common mixtures on a national scale may differ from those on a regional or local scale; consequently, there is also a need to conduct smallerscale studies such as was done in southern New Jersey (8). Common mixtures in groundwater may not be the most toxic from a health perspective, but human exposure to these mixtures is prevalent.…”
Section: Introductionmentioning
confidence: 99%